When is an international branch campus? - Healey, Nigel (International Higher Education, 2014)
There are an estimated 200 international branch campuses around the world. As these campuses evolve in response to the changing regulatory and competitive environment, trying to get a clear-cut definition of an international branch campus is becoming increasingly difficult. Instead of asking ‘what is a branch campus?’ it is more interesting to consider when—at what point the operation ceases to be a foreign subsidiary of the home university in any meaningful sense.